Role of foliar fungal endophytes in litter decomposition among species and population origins - Gundel, Pedro E. (2016)
Fil: Gundel, Pedro E. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas vinculadas a la Agricultura; Argentina.